25 Patients treated with long term warfarin therapy undergoing PCI – complex disease and adverse outcomes. (24th April 2016) - Yazji, Khaled; Kakhi, Sorayya; Ossei-Gerning, Nick; Choudhury, Anirban; Anderson, Richard; Kinnaird, Tim
Abstract : Introduction: Patients treated with warfarin who undergo percutaneous coronary intervention (PCI) present a difficult therapeutic problem. Their baseline demographics, procedural characteristics and 12-month outcomes are poorly defined. Methods: We conducted a retrospective analysis of all patients who underwent PCI at a major UK cardiac centre between 2012 and 2013. Of the 2675 patients who underwent PCI, 155 were on long-term warfarin (5.8%). Patients on warfarin were older and more likely to have significant comorbidity than patients not on warfarin. Results: The Mehran bleed scores (19.0 ± 5.8 vs. 15.4 ± 8.0, p = 0.004) and baseline SYNTAX scores (18.5 ± 9.1 vs. 12.4 ± 3.8, p = 0.0006) were higher in patients treated with warfarin vs. those not treated. Bare metal stents were more frequently utilised in warfarin patients than non-warfarin patients (44.8 vs. 26.3%, p < 0.0001) and residual SYNTAX scores were higher (8.3 ± 1.1 vs. 3.8 ± 5.9, p = 0.001). Anti-platelet mono-therapy was prescribed after PCI in 14.4% of warfarin patients and 0.7% of non-warfarin (p < 0.0001) whilst mean DAPT duration was also significantly shorter (4.3 vs. 10.7 months, p < 0.0001). At 1-year follow-up TVR (6.5 vs. 3.3%, p < 0.05), stent thrombosis (5.0 vs. 2.6%, p = 0.14), death (10.1 vs. 4.6%, p < 0.01) and TVR/ST/death (21.6% vs. 10.5%, p = 0.004) were all more common in the warfarin cohort. Conclusion: In conclusion patients treated with warfarin who undergo PCI are a complex cohort and are more likely to receive incomplete revascularisation, less intense and shorter durations of anti-platelet therapy and have adverse 1-year outcomes.